The Use of Digital Peripheral Artery Tonometry to Detect Endothelial Dysfunction in Pregnant Women Who Smoke - Pearce, Christy F.; Lain, Kristine; Hansen, Wendy F.; Curry, Thomas, Jr; O'Brien, John M. (American Journal of Perinatology, 2014)
Objective We hypothesized that, as has been shown outside of pregnancy, endothelial dysfunction would be seen in a dose-dependent fashion among women who smoke in the midtrimester of pregnancy.Study Design Endothelial function in women with singleton pregnancies between 16 and 23 weeks was analyzed utilizing the Endo-PAT2000 device (Itamar Medical Ltd., Caesarea, Israel) and expressed as a reactive hyperemia ratio (RHI). Serum was drawn to check cotinine and high-sensitivity C-reactive protein (CRP) levels. SAS 9.2 (SAS Institute, Cary, NC) was used to perform statistical tests including Student t test, analysis of variance, Fisher exact test, and Pearson coefficient.Results Endothelial function was noninvasively examined in 29 smokers and 31 nonsmokers. Demographics including age, race, and parity were similar between groups. Mean RHI was not significantly different between smokers and nonsmokers (1.43 ± 0.32 versus 1.53 ± 0.39, p = 0.27). No correlation was noted when cotinine values were plotted against RHI or CRP values in smokers (rho = 0.24, p = 0.21 and rho = 0.26, p = 0.18, respectively). RHI did correlate with diastolic blood pressure (rho = −0.40, p = 0.002), systolic blood pressure (rho = −0.35, p = 0.006), and heart rate (rho = −0.37, p = 0.004).Conclusion We did not find an association between smoking status and endothelial dysfunction in the midtrimester utilizing a noninvasive methodology.
Keywords: endothelium; pregnancy; smoking; noninvasive testing